Modeling of water tree degradation in underground polymeric power cable using time domain reflectometry method [electronic resource] - Azniza Ahmad, 1987- author; Yanuar Zulardiansyah Arief; Fakulti Kejuruteraan Elektrik (2015)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2015